Teknologi React Native Pada Aplikasi Mobile Pemilihan Anggota Terbaik dan Pencatatan Point Bank Sampah - Anggraini Kusumaningrum; Diki Zulkifli; Yuliani Indrianingsih; Asih Pujiastuti (Jurnal Teknologi Informasi dan Terapan, 2022)
The increase in people's consumption patterns in the Kalirejo area, Central Lampung has an impact on increasing the volume of waste. The Sidodadi Trash Bank is an alternative in the context of waste management at the community level. Sidodadi Trash Bank in its management requires recording activities and rankings for all its members which are calculated every year with the aim of providing rewards for the best members. Recording and ranking activities are still done manually, therefore a Decision Support System (SPK)-based application is presented to facilitate the activities of the Sidodadi Trash Bank. This application can be used for administrators and also all members of the Sidodadi Trash Bank. This application was created using visual studio software and Simple Additive Weighting (SAW) method. The results of the calculation of the SAW method on the data of five members manually proved to be the same as the results of the system calculations, namely 0,99, which was won by Novita Sari. Testing Device was carried out on Android versions 7.1.1 Nougat, 7.1.2 Nougat, 8.0.0 Oreo, 8.1 Oreo, and 9.0.0 Pie and all worked. From the test results, it is found that the application runs well at least on the Android 5.0 Lollipop version.